Social Health Insurance Reexamined - Wagstaff, Adam (2012)
Social health insurance (SHI) is enjoying something of a revival in parts of the developing world. Many countries that have in the past relied largely on tax finance (and out-of-pocket payments) have introduced SHI, or are thinking about doing so. And countries with SHI already in place are making vigorous efforts to extend coverage to the informal sector. Ironically, this revival is occurring at a time when the traditional SHI countries in Europe have either already reduced payroll financing in favor of general revenues, or are in the process of doing so. This paper examines how SHI fares in health care delivery, revenue collection, covering the formal sector, and its impacts on the labor market. It argues that SHI does not necessarily deliver good quality care at a low cost, partly because of poor regulation of SHI purchasers. It suggests that the costs of collecting revenues can be substantial, even in the formal sector where nonenrollment and evasion are commonplace, and that while SHI can cover the formal sector and the poor relatively easily, it fares badly in terms of covering the nonpoor informal sector workers until the economy has reached a high level of economic development. The paper also argues that SHI can have negative labor market effects.